A note on divergent mtDNA lineages of bottlenose dolphins from coastal waters of southern Australia - Charlton , Kate; Taylor , Andrea C.; McKechnie , Stephen W. (J. Cetacean Res. Manage., 2023)
Bottlenose dolphins have a global distribution throughout tropical and temperate waters, both inshore and offshore. Many studies demonstrate the existence of at least two Tursiops species: Tursiops truncatus, consisting of inshore and offshore eco-types and T. aduncus, a coastal Indo-Pacific type known to extend south into temperate waters down the east coast of Australia. To clarify the taxonomic status of two populations (Port Phillip Bay and Gippsland Lakes) of coastal bottlenose dolphins along Australia’s south coast (Victoria), a 346bp region of the mitochondrial-DNA (mtDNA) control region was sequenced from ten individuals and they were incorporated into phylogenetic analyses involving published sequences of other Tursiops spp., Stenella spp. and Delphinus spp., found worldwide. Both neighbour-joining and maximum parsimony trees place Victorian coastal haplotypes in a highly-supported group separate to those from the other dolphins, including those from the southern part of the Australian eastern coast. Victorian haplotypes are least divergent from T. truncatus (average 5.5%) and most divergent from T. aduncus (9.1%), with intermediate levels of divergence from Stenella and Delphinus spp. These data suggest that the Victorian coastal dolphins, similar to other world-wide coastal populations, are genetically unique, long isolated and therefore likely to be locally adapted. This has important implications for management and conservation.